The Utilisation Of Wood Ash As Alkaline Activator For Ambient Cured Geopolymer Concrete - Samsudin, Muhammad Hasnolhadi (2020)
The study was conducted with the primary aim to hybridise industrial waste ash namely pulverised fuel ash (PFA), ground granulated blast furnace slag (GGBS), high calcium wood ash (HCWA) and silica fume (SF) with suitable alkaline activators to produce binder for concrete.